Evaluating the Risk of Social Isolation in Older People: AHP-Fuzzy Comprehensive Evaluation - Li W; Yin H; Song Y; Tu W; Wang L; Liang Y; Bai Y; Xu G (Dove Medical Press, 2023)
Weitong Li,1,* Haiyan Yin,1,* Yulei Song,1 Wenjing Tu,1 Lulu Wang,1 Yongqi Liang,1 Yamei Bai,1,* Guihua Xu2,* 1School of Nursing, Nanjing University of Chinese Medicine, Nanjing, People's Republic of China; 2Nanjing University of Chinese Medicine, Nanjing, People's Republic of China*These authors contributed equally to this workCorrespondence: Guihua Xu, Nanjing University of Chinese Medicine, Nanjing, People's Republic of China, Email 7115@njucm.edu.cnBackground: Social isolation is a serious and pervasive health issue among older people, and it is difficult to identify and assess effectively. Based on a thorough and scientific evaluation index system, AHP-Fuzzy comprehensive evaluation could be a valuable technique.Objective: It is crucial to establish interventions that focus on risk factors for the prevention of social isolation in order to give a strong scientific foundation for enhancing older people's health habits. This can be achieved by using a fuzzy comprehensive evaluation method to assess the risk of social isolation in older people.Methods: A hundred community members over 60 from Nanjing were selected as the evaluation subjects in China. After the element layer was split into three categories of "social risk, economic risk, and cultural risk" using the analytic hierarchy process approach, a total of 22 assessment indicators were picked to develop a risk evaluation index system.Results: The risk level of social isolation belonging to the "low risk, relatively low risk, medium risk, relatively high risk, high risk" of membership degree are respectively " 0.3392, 0.2632, 0.2257, 0.1069, 0.0650". Fuzzy comprehensive evaluation analysis showed that social relations (0.4934), monthly income (0.4654), health status (0.5960) were significant factors of social isolation risk in older people. The results showed that factors related to social risk had the most significant impact on social isolation.Conclusion: It is scientific and feasible to construct the risk evaluation index model of social isolation risk for the elderly by using AHP-Fuzzy comprehensive evaluation method. In preventing social isolation of older people in the future, we should pay attention to the impact of social and cultural factors on them, and provide practical intervention programs and references from the government, community, family.Keywords: AHP, fuzzy comprehensive evaluation method, social isolation, older people